Objective assessment of surgeon’s psychomotor skill using virtual reality module - Siti Nor Zawani Ahmmad; Eileen Su Lee Ming; Yeong Che Fai; Suneet Sood; Anil Gandhi; Nur Syarafina Mohamed; Hisyam Abdul Rahman; Etienne Burdet (Institute of Advanced Engineering and Science, 2019)
This study aims to identify measurable parameters that could be used as objective assessment parameters to evaluate surgical dexterity using computer-based assessment module. A virtual reality module was developed to measure dynamic and static hand movements in a bimanual experimental setting. The experiment was conducted with sixteen subjects divided into two groups: surgeons (N = 5) and non-surgeons (N = 11). Results showed that surgeons outperformed the non-surgeons in motion path accuracy, motion path precision, economy of movement, motion smoothness, end-point accuracy and end-point precision. The six objective parameters can complement existing assessment methods to better quantify a trainee’s performance. These parameters also could provide information of hand movements that cannot be measured with the human eye. An assessment strategy using appropriate parameters could help trainees learn on computer-based systems, identify their mistakes and improve their skill towards the competency, without relying too much on bench models and cadavers.